A psychoanalytic view of the current economic and social crisis: the model of perversion - Ζερβός, Κώστας (The Greek Review of Social Research, 2011)
The concept of perversion is suggested as a metaphor to describe basic aspects of contemporary economic and social crisis. The evolution of the theories that connect the basic psychoanalytic concepts with the social is described and the clinical entity of perversion in psychoanalytic theory is analysed. Two examples of perverse way of thinking («I know well…, however…») in the social context are given.